Effect of single nucleotide polymorphisms of CAPN1 and CAST genes on meat traits in Nellore beef cattle (Bos indicus) and in their crosses with Bos taurus - Curi, Rogerio Abdallah [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; Mason, M. C. [UNESP]; Arrigoni, Mario de Beni [UNESP]; Silveira, Antonio Carlos [UNESP]; Oliveira, Henrique Nunes de [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>The objectives of this work were to study the segregation of single nucleotide polymorphisms of the calpain 1, large subunit (CAPN1) and calpastatin (CAST) genes in Nellore (Bos indicus) and Nellore xBos taurus beef cattle, as well as to evaluate their effects on meat traits. For this, 300 animals, including 114 Nellore, 67 Angus x Nellore, 44 Rubia Gallega x Nellore, 41 Canchim, 19 Brangus three-way crosses and 15 Braunvieh three-way crosses, were genotyped for the CAPN4751 [AF_248054.2:g.6545C > T (GenBank accession AF248054.2)] and CAST/DdeI [AF_159246.1:g.2959A > G (GenBank accession AF159246.1)] polymorphisms and phenotyped for Ribeye Area, Backfat Thickness, Intramuscular Fat, Shear Force (SF) and Myofibrillar Fragmentation Index (MFI). In relation to the CAPN4751 polymorphism, a frequency of 10.5% was observed for the C allele in the Nellore breed. In the total sample of studied animals, a significant association was found between genotypes and meat tenderness, assessed by SF (P = 0.005) and MFI (P = 0.008), with genotype CT being more favourable than TT. For the CAST/DdeI polymorphism, a frequency of 55.7% was found for the A allele in the Nellore breed. In the total sample, a significant association was observed between genotypes and meat tenderness - SF (P = 0.004) and MFI (P = 0.006), with genotype AA being more favourable than AG. The relationship between genotypes and aged meat tenderness in confluence with the distribution of favourable alleles shows great potential for application of the CAPN4751 and CAST/DdeI polymorphisms in the genetic improvement of the Nellore breed, whilst contributing to the validation, in this breed and in its crosses with B. taurus, of the association results previously described in the literature.
Keywords: calpain; calpastatin; meat tenderness; polymorphism; zebu